2016
DOI: 10.1086/687293
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxidized Lipids in Pulmonary Arterial Hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a multifactorial disease characterized by interplay of many cellular, molecular, and genetic events that lead to excessive proliferation of pulmonary cells, including smooth muscle and endothelial cells; inflammation; and extracellular matrix remodeling. Abnormal vascular changes and structural remodeling associated with PAH culminate in vasoconstriction and obstruction of pulmonary arteries, contributing to increased pulmonary vascular resistance, pulmonary hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 158 publications
(311 reference statements)
6
29
1
Order By: Relevance
“…Notably each of these risk factors pathologically disrupts the lipidome and this disruption may be a unifying feature of severe COVID-19. [1][2][3][4][5][6][7] Here we provide the first in depth interrogation of lipidomic changes, including structural-lipids as well as the eicosanoids and docosanoids lipid mediators (LMs), that mark COVID-19 disease severity. Our data reveal that progression from moderate to severe disease is marked by a loss of specific immune regulatory LMs and increased pro-inflammatory species.…”
Section: Introductory Paragraphmentioning
confidence: 99%
“…Notably each of these risk factors pathologically disrupts the lipidome and this disruption may be a unifying feature of severe COVID-19. [1][2][3][4][5][6][7] Here we provide the first in depth interrogation of lipidomic changes, including structural-lipids as well as the eicosanoids and docosanoids lipid mediators (LMs), that mark COVID-19 disease severity. Our data reveal that progression from moderate to severe disease is marked by a loss of specific immune regulatory LMs and increased pro-inflammatory species.…”
Section: Introductory Paragraphmentioning
confidence: 99%
“…25) Previous studies also re- vealed that excessive ROS generation reduced nitric oxide levels and induced proliferation and hypertrophy of pulmonary arterial smooth muscle cells, and eventually enhanced vasoconstriction and pulmonary vascular remodeling. 26,27) Aside from the adverse effects of ROS, the upregulation of vascular NADPH oxidase evoked proliferation and apoptosis-resistance of the pulmonary arterial wall cells. 2) In this study, our data showed that the MDA level and NADPH oxidase expression were significantly increased in MCT-induced pulmonary hypertension rats, and AOS reduced the MCT-induced MDA production and NADPH oxidase expression.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data give evidence of major involvement of inflammation mediators and their synthesizing proteins (such as LTs synthetized by 5-LO) in PAH and make them attractive pharmacological targets to counteract PAH pathology (Sharma et al, 2016). Within the context of our investigations toward the synthesis of different compound libraries with prospects for therapeutic use, we recently studied the natural and synthetic quinone derivatives.…”
Section: Introductionmentioning
confidence: 98%
“…It has been observed that in some patients, inflammation appears to play a major pathogenic role (Nicolls et al, 2005;Hassoun et al, 2009), activation of inflammatory cells and increased production of their mediators are important features of PAH (Price et al, 2012). In fact, higher circulating levels of monocyte chemoattractant protein 1 (MCP-1), tumor necrosis factor a (TNF-a), and interleukins in patients with idiopathic PAH than in healthy controls are involved (Kimura et al, 2001;Itoh et al, 2006;Sanchez et al, 2007;Zabini et al, 2014;Sharma et al, 2016). Macrophages, in particular, are prominent components of the inflammatory infiltrates in the lungs of patients and animals with PAH (Tuder and Voelkel, 1998;Dorfm ller et al, 2003;Taraseviciene-Stewart et al, 2007;Tamosiuniene et al, 2011).…”
Section: Introductionmentioning
confidence: 99%